North–South Scholarly Collaboration: Opportunities and Experiences in Africa. Issue 1 (13th October 2021) - Sonnenwald, Diane H.; Rorissa, Abebe; Fourie, Ina; Julien, Heidi; Raju, Jaya; Alemneh, Daniel
Abstract: North–South scholarly collaboration and academic exchange programs help to address the challenges experienced by developing countries in Africa and elsewhere, and provide unique benefits to scholars in developed countries. Many academics in the global north, however, have limited, or no, information about opportunities to visit academics and institutions in developing countries and those in such countries in the global south do not have contacts to whom they can reach out. The intention of the panel is to stimulate future north–south collaborations by increasing awareness of both funded opportunities and low budget initiatives for scholarly exchanges and collaborations, benefits for scholars and their institutions in developed and developing countries, and best practices with respect to north–south collaborations and scholarly exchanges. This panel is sponsored by the Africa Chapter and SIG‐III.